Group Psychoeducation for Anxiety Symptoms in Youth: Systematic Review and Meta-analysis. Issue 1 (2nd January 2022) - Baourda, Vasiliki C.; Brouzos, Andreas; Mavridis, Dimitris; Vassilopoulos, Stephanos P.; Vatkali, Effrosyni; Boumpouli, Christina
ABSTRACT: This systematic review and meta-analysis aims to provide a comprehensive evaluation of randomized controlled trials of psychoeducational group interventions targeting anxiety symptoms in youths. We systematically searched for articles and located twelve studies that collectively included 1132 subjects. Analyses showed an overall effect of −0.47 (95% CI −0.75 to −0.19) on the Standardized Mean Difference (SMD) scale, suggesting that psychoeducation effectively reduces anxiety symptoms in children and adolescents. However, the I 2 index was 86.4% revealing the presence of substantial heterogeneity. These results suggest that psychoeducation may be a promising alternative for the prevention and/or treatment of anxiety disorders in youths.